The UNSCOM Saga - Pearson, Graham S. author. aut Link
XXIII, 255 p. 4 illus.
Keywords: This authoritative account details the doggedly persistent work of the UNSCOM (United Nations Special Commission) on Iraq which has during the past eight years, in the face of continued Iraqi deception, gradually uncovered more and more of the scope of the Iraqi chemical and biological weapons programmes and established an ongoing monitoring and verification regime. Vital lessons are drawn for international security and for the strengthening of the non-proliferation regimes for both chemical and biological weapons.